Why do trade negotiations take so long? - Christoph Moser; Andrew K. Rose (ETH Zurich, KOF Swiss Economic Institute, 2012)
The Doha multilateral round of trade negotiations sponsored by the WTO has been dragging on for over a decade, with no end in sight. In this short paper we assess empirically what determines the duration of trade negotiations, focusing on the span between the start of trade talks and their conclusion. We use data from 88 regional trade agreements between 1988 and 2009, and a semi-parametric Cox proportional hazards model. Four factors are robust determinants of the length of RTA negotiations. Negotiations are more protracted when there are more countries at the negotiation table, and when the countries are not from the same region. Negotiations between more open and richer countries are also finished more quickly.
Keywords: F13; F51; F53; 330; regional; GATT; WTO; duration; income; data; empirical; Cox; survival; Handelsabkommen; WTO-Regeln; Politische Entscheidung; Dauer; Welt